SYSTEMATIC REVIEW: DETERMINANTS OF PATIENT SATISFACTION WITH HOSPITAL SERVICES - Ni Putu Deni Adi; Yaslis Ilyas (Proceedings of the International Conference on Applied Science and Health, 2019)
Background: Satisfactory and quality service will shape patient or customer loyalty, and satisfaction is closely related to "word of mouth". The next effect will be on the process of forming an image of an increasing hospital. This is due to very tight competition conditions. So each hospital will try to put itself as best as possible in the eyes of patients / customers to be trusted to meet their needs in the health sector. Usually health care satisfaction is the highest level of satisfaction above 85%. Research is needed on the determinants of patient satisfaction with hospital services as a reference for improving the quality of hospital services. Objectives: To determine the determinant of patient satisfaction with hospital services. Method: A systematic review through journal review regarding the determinants of patient satisfaction with hospital services. Search articles accessed from internet databases, namely: ProQuest for English language publications, overall from abroad, last 12 months, using a combination of search terms " Patient satisfaction, determinants, hospital ", article selection using screening. Qualitative thematic analysis is used for synthesis. Result:. The similar key findings from the 10 papers are empathy or interpersonal relations becomes a determinant that dominates the increase in patient satisfaction with hospital services. Empathy is a channel of efficient communication with patients and is also considered an important determinant of clinical outcomes. Conclusions: 10 studies included in this systematic review show the similar key findings. empathy or interpersonal relations becomes a determinant that dominates the increase in patient satisfaction with hospital services. As a recommendation for further research, it is necessary to search for the determinants of patient satisfaction with hospital services through several data bases to obtain more information about the determinants of patient satisfaction with hospitals.